Beyond medications: a multifaceted approach to alleviating comorbid anxiety and depression in clinical settings - Svensén, Sofia; Bolstad, Ingeborg; Ødbehr, Liv Skomakerstuen; Larsson, Gerry (Frontiers in Psychology, 2024)
Background Comorbid anxiety and depression are common and can make the problems more complex and sometimes resistant to pharmacological treatment. In existing research, the diagnoses are often studied separately, and physical activity, healthy nutrition, psychoeducation, and social support have shown good effects. The aim of the present study was to explore the longitudinal effects of a comprehensive treatment on patients with comorbid anxiety and depression in a clinical context. Method Eighty inpatients (15 men and 65 women) in age range 23–65 years receiving psychiatric treatment in Norwegian clinic participated in the longitudinal study. Treatment was person-centered and was most frequently given for anxiety and depression, e.g., pharmacological treatment and psychotherapy, individually and in groups. In combination with this, physical activity, healthy nutrition, psychoeducation and social support in contacts with authorities and relatives were also a part of treatment. Depression and anxiety were assessed using the Beck Anxiety Inventory and Beck Depression Inventory at three points in time: baseline, at the end of treatment, and 3 months after treatment. The answers were categorized and combined into four groups according to severity of anxiety and depression to measure effects on comorbidity. Mann Whitney U test, Chi-square, Friedmans test, and McNemar test were used to analyze the data. Result The results showed a significant increase of frequencies in the group with mild anxiety and depression 3 months past treatment compared to baseline. Conclusion Through the comprehensive, person-centered treatment more patients had low levels of both anxiety and depression 3 months after treatment. We suggest that clinics working with comorbid depression and anxiety patients should add physical activity, nutrition advice, social support, and psychoeducation to the traditional treatment regimes. More research concerning comorbid anxiety and depression are urgent to further expand the treatment possibilities.